Pemberdayaan Advertensi Digital Produk UMKM Berbasis Media Sosial Di Kelurahan Bahagia, Babelan, Bekasi - Eriyani, Reni Nur; Murtadho, Fathiaty; Anwar, Miftahulkhairah; Utami, Sintowati Rini; Haikal, Muhammad Saddam; Azmuna, Nurieyya Fieka; Ayu, Deafitri Puspa (Universitas Nusantara PGRI Kediri, 2023)
Internet has considerable potential as a medium of marketing and commerce, particularly in the field of advertising. Unfortunately, advertising through internet, especially social media in Indonesia has not been optimized. Therefore, UMKM activists need training on the role of digital advertising through social media. The aim of this social responsibility is to provide training on digital advertisement through social media. The output of this activity is to introduce and utilize social media as a medium to develop, expand, and optimize digital advertising that will contribute to increasing UMKM trade.